Assessing the Practices for the Conduct of Graduate Students’ Thesis at the Faculty of Management and Development Studies, UP Open University - Garcia, Primo G.; Buno, Grace Anne C.; Bagos, Jelaine R. (International Journal on Open and Distance e-Learning, 2018)
Graduate student thesis practices are procedures and policies that are followed by graduate students, faculty members, and staff of higher education institutions. Since UP Open University (UPOU) is an Open and Distance e-Learning (ODeL) institution, the thesis practices that are implemented by its Faculty Offices must adhere to the principles of distance education. Appropriate implementation of graduate thesis production at UPOU requires closer coordination because of the time and space difference between and among advisers, students, staff, panel members, and program chair. The practices comprising graduate student thesis writing in the UPOU Faculty of Management and Development Studies (FMDS) Programs are here explored. The study examines the administrative practices followed by the programs of FMDS in the conduct of graduate thesis among its learners. Practices that contribute to quality thesis administration are suggested here. These suggestions follow those available in the literature and those uncovered from thesis students’ experiences. Finally, this inquiry presents recommendations that will promote good practices in administering the programs’ thesis courses in the distance mode.